The performance of epic songs in funeral contexts - Jiga Laura; International Ballad Conference (31.) (2001) (Budapest) (2002)
“All that an old song tells, really happened.” One of the traditional functions of performing epic songs is that of evoking the past. The act of performing is invested with the value of empathic communication with “old times” and with the ancestors.The agent who mediates between the audience and those who are evoked is the fiddler. These facts may place the performance in a context with a sacred dimension and funeral meanings. Being involved in this specific act of communication, the audience has to play an active role. It has to be trained in “listening”. The traditional coordinates of performing epic songs have changed. The category of epic song entered the passive repertoire of folklore. Using a questionnaire and interviews the author, together with a group of students, tried to draw the status of performing epic songs in Romanian contemporary society.
Keywords: Társadalomtudományok; Szociológia